Framing conflict – the Cold War and after: Reflections from an old hack. (April 2017) - Somerville, Keith
The media – whether mainstream press, broadcasting and online services or social media – is still a major source of news about conflicts for the majority of people. They rely on the media to tell them what is going on in the world, select what is important or relevant and exclude the items that are deemed unimportant or unintelligible. The media uses forms of representation and framing to simplify and provide recognized depictions of distant countries, peoples and wars. These are part of the basic operating procedures of media organizations. But do they conceal or exclude more than they explain and do they give an accurate picture of the causes and combatants? Based on 40 years of monitoring, reporting and putting together news programmes on conflicts across the globe, the author seeks to analyse how framing works and the distortions in understanding that it leads to. The author gives his perspective on the five decades of conflict in Angola and the way framing has changed but done little to inform or educate.